Entrepreneurship through Technical Institutions- A Pragmatic Approach - Kumar, Pawan; Kumar , Suresh (Gyan Management Journal, 2008)
Around the world entrepreneurship and enterprise education beginning to take hold. nation· ability to generate a Stead tream of business opportunities can onl ’ come out when its people take to entrepreneurial acti itie . ln Malaysia, Russia, Australia and many countries in central and Eastern Europe course with entrepreneurial education ha e been incorporated in schools and te hnicaJ education curricula. In Denmark in 1996, ministry of education ha decided a two year action programme to enhance motivation among young people to set up their own_ business and to promote entrepreneurial attitude.